Seed dispersal and realized gene flow of two forest orchids in a fragmented landscape - Kotilínek, Milan (Jihočeská univerzita, 2021)
This thesis investigates the dispersal abilities of mycoheterotrophic plants represented by three orchid species. Seed trapping and gene flow study were used to examine this topic.
Seed dispersal and realized gene flow of two forest orchids in a fragmented landscape
Keywords: Cephalanthera rubra; Epipactis atrorubens; fragmented landscape; gene flow; microsatellite DNA markers; seed dispersal; seed traps; Cephalanthera rubra; Epipactis atrorubens; fragmented landscape; gene flow; microsatellite DNA markers; seed dispersal; seed traps